An unusual presentation of Huntington's disease. Issue 7 (16th July 2021) - Schulze Westhoff, Martin; Osmanovic, Alma; Meissner, Catharina; Heck, Johannes; Mahmoudi, Nima; Hendrich, Corinna; Berding, Georg; Seifert, Johanna; Bleich, Stefan; Frieling, Helge; Krüger, Tillmann; Groh, Adrian
Abstract: We describe the case of a 59‐year‐old woman who exhibited psychotic symptoms, cognitive dysfunction, and restlessness. While the clinical picture and 18F‐FDG PET/CT suggested the presence of a tauopathy, especially frontotemporal dementia or progressive supranuclear palsy, genetic testing eventually revealed Huntington's disease. Abstract : We describe the case of a 59‐year‐old woman who exhibited psychotic symptoms, cognitive dysfunction, and restlessness. While the clinical picture and 18F‐FDG PET/CT suggested the presence of a tauopathy, especially frontotemporal dementia or progressive supranuclear palsy, genetic testing eventually revealed Huntington's disease.